Instrumento de avaliação biopsicossocial para estudantes com TEA (IABA=TEA): elaboração e aplicação inicial - Zamboni, Monithielly Regina (Universidade Federal de São Carlos, 2025)
Students with Autism Spectrum Disorder (ASD) face numerous barriers related to social interaction, communication, and the learning process, requiring appropriate assessment procedures and specialized support. Given this, the guiding question of the study was: How can students with ASD be assessed from the perspective of the biopsychosocial model? Therefore, the main objective of this research was to design and apply an assessment instrument for students with ASD based on the biopsychosocial model. To achieve this goal, an exploratory study was conducted using a mixed-methods approach (qualitative and quantitative). The instrument, named IABA-ASD, was based on the International Classification of Functioning, Disability and Health (ICF) and its Core Sets for ASD, proposed by the World Health Organization. Data collection took place in a municipality in the interior of Paraná, Brazil. A survey was conducted, grounded in the biopsychosocial model: the context of students with ASD was evaluated by family members, teachers, the multidisciplinary team, and school administrators. A specific questionnaire was developed for each group: IABA-ASD Family, IABA-ASD Teachers, IABA-ASD Administrators, and IABA-ASD Multidisciplinary Team. The results showed that: (I) The development and application of the IABA-ASD enabled the assessment of Special Educational Services from a holistic perspective, identifying both critical aspects (barriers) and potential aspects (facilitators) that influence the learning and inclusion of students with ASD; (II) The instrument represented a significant contribution, given the scarcity of assessment tools aligned with the ICF’s biopsychosocial model; (III) The IABA-ASD proved to be effective in providing support for teachers and administrators in the development of individualized intervention plans, as well as in guiding potential community-level actions and inclusion policies; (IV) The study revealed a limitation regarding the instrument’s application due to the small number of participating students in school settings. Further research is recommended to support the validation of the IABA-ASD in diverse educational contexts
Biopsychosocial assessment instrument for students with ASD (IABA=TEA): preparation and initial application
Keywords: Educação especial; Transtorno do espectro autista; Atendimento educacional especializado; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO